2018
DOI: 10.1111/jgh.14464
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of cold versus hot snare polypectomy: A meta‐analysis

Abstract: Cold snare polypectomy is a safe, efficient, and effective polypectomy technique for diminutive or small colorectal polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 30 publications
4
80
1
Order By: Relevance
“…Furthermore, the incomplete resection rate of CFP was significantly higher than that of CSP. These results are comparable with those of a previous systematic review and meta-analysis [7][8][9][10][11]. However, we performed a subgroup analysis stratified by polyp size, which was not performed in previous reports.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the incomplete resection rate of CFP was significantly higher than that of CSP. These results are comparable with those of a previous systematic review and meta-analysis [7][8][9][10][11]. However, we performed a subgroup analysis stratified by polyp size, which was not performed in previous reports.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, trials comparing the effects and risks of CSP and hot snare polypectomy (HSP) or endoscopic mucosal resection (EMR) for colorectal polyps ! 10 mm have been reported, and systematic reviews with meta-analyses that integrated those trials have been published [7][8][9]. However, the polyp size was not evaluated in these studies, and no metaanalysis analyzed the influence of the polyp size.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, with cold snare resection there is no coagulated eschar formation, thus significantly reducing the delayed bleeding from sloughing. For lesions <10 mm, a shorter procedural time has already been demonstrated, 27,28 and the gain could theoretically be greater for larger lesions.…”
Section: Discussionmentioning
confidence: 93%
“…Most polyps encountered during colonoscopy are either diminutive (<5 mm) or small (6-9 mm) nonpedunculated polyps. The current ESGE guidelines 32 recommend CSP as the preferred technique for the removal of subcentimeter (<10 mm) polyps, with a recent meta-analysis 33 supporting this recommendation. A recent multicenter randomized controlled trial 34 showed that CSP is not inferior (comparable resection rate) to HSP for small nonpedunculated polyps with a superior safety profile (lower delayed PPB rate).…”
Section: Prevention Of Post-polypectomy Bleedingmentioning
confidence: 98%